Navigating Challenges: Herdsmen-Crop Farmers Conflict and its Effect on Yam Productivity in Benue State - Oriko, Sylvanus Ekonesie; Ismaila, M Dankogi; Ogbaini, Clement Aliu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The conflict between herdsmen and crop farmers in Nigeria has significantly impacted the productivity of yam farmers in the Logo Local Government Area of Benue State. The study investigated this conflict's impact on yam farmers' productivity. Data was collected from a structured questionnaire administered to 400 households affected by the conflict. The study found that the conflict negatively impacts the productivity of yam farmers in the Logo Local Government Area. The study reveals that 67.3% of yam farmers in Benue State are male, with a mean age of 35. The majority are married, have an average household size of 11 people, and have a small-scale farm size. Their low education level may contribute to unabated conflict dynamics. The study reveals that herdsmen attacks significantly reduce the productivity of yam farmers in the study area, with a higher number of respondents producing more output before the attacks and a lower number after the attacks. The logit regression model shows that Fulani attacks, attacks by Fulani herdsmen, and technology led to significant deaths in households, reducing the labour force, destroying farmers' inputs, and instilling terror. In conclusion, the study reveals that herdsmen attacks have significantly reduced the productivity of yam farmers in the study area, affecting not only the labour force but also their inputs and livelihoods, highlighting the detrimental impact of conflict-related violence. It was recommended that the government should also provide easy access to finance for farmers affected by this conflict to recover their lost farm capital.